EXPLORATION OF STUDENTS' EXPERIENCES IN USING DIGITAL STORYBOOKS TO INCREASE INTEREST IN READING AT SMP NEGERI 1 TONGAUNA - Sukmawati Sukmawati; Afni Afni (JURNAL ILMIAH NUSANTARA, 2025)
The development of digital technology has brought significant changes in the world of education, including in the provision of reading materials that are more interactive and flexible. One of the innovations utilized in increasing students' interest in reading is the use of digital storybooks. This study aims to explore students' experiences in using digital storybooks and identify the supporting and inhibiting factors in increasing interest in reading. This study used a qualitative approach, which was conducted at SMP Negeri 1 Tongauna involving 25 students of class VIII A as research subjects. Data collection techniques included observation, questionnaires, documentation, and data triangulation through interviews with teachers. The results showed that most students felt a more interesting, comfortable, and enjoyable reading experience through digital storybooks compared to printed books. Supporting factors include attractive visual displays, ease of access, interactive features, and support from teachers and school infrastructure. Meanwhile, inhibiting factors include technical constraints, distractions from social media, and physical discomfort such as eyestrain. The findings suggest that digital storybooks have great potential to increase students' interest in reading if supported by a conducive learning environment and appropriate technology utilization strategies.